2007
DOI: 10.1002/ldr.831
|View full text |Cite
|
Sign up to set email alerts
|

Changes in copper content and distribution in young, old and abandoned vineyard acid soils due to land use changes

Abstract: We studied total Cu content and its distribution in 33 surface soil samples cultivated with vines for variable lengths of time in the Monterrei designation of origin (DO), located in Galicia (NW Spain). The study was focused on the influence of land use changes on soil degradation by effect of Cu accumulation and availability. Total copper concentration in soils ranged from 25 to 272 mg kg À1 . The time during which each soil was cultivated with vines was found to affect both the total concentration of copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
34
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 46 publications
7
34
0
Order By: Relevance
“…3). These exchangeable Cu values are similar to those obtained in other studies focused on Cu fractionation in vineyard soils, which reported absolute values usually below 10 mg kg −1 and a percentage of about 5% of Cu T (Parat et al, 2002;Arias et al, 2004;Fernández-Calviño et al, 2008d). Since Cu EX is considered the most mobile fraction in the soil, our results suggest that only a small amount of Cu could be mobilized to soil solution.…”
Section: Copper Distribution In Soilssupporting
confidence: 91%
“…3). These exchangeable Cu values are similar to those obtained in other studies focused on Cu fractionation in vineyard soils, which reported absolute values usually below 10 mg kg −1 and a percentage of about 5% of Cu T (Parat et al, 2002;Arias et al, 2004;Fernández-Calviño et al, 2008d). Since Cu EX is considered the most mobile fraction in the soil, our results suggest that only a small amount of Cu could be mobilized to soil solution.…”
Section: Copper Distribution In Soilssupporting
confidence: 91%
“…Vine is among the crops most strongly affected by the use of pesticides [6], which, however, also affect hops [7], avocado [8], coffee [9] and cocoa plants [10].…”
Section: Introductionmentioning
confidence: 99%
“…The velocity of each raindrop at the point of impact and the kinetic energy were calculated for raindrops falling from 1-and 2.5-m heights (Epema and Riezebos, 1983) and they are shown in Table 1. An equivalent diameter was also calculated for the same fall heights by P erez- Rodríguez et al (2013a).…”
Section: Raindrop Simulatormentioning
confidence: 99%